Problem-oriented Management of United Territorial Communities’ Development Based on Decentralization under the Pandemic Influence - Ivanov Yuriy (EDP Sciences, 2021)
The article is devoted to the problem-oriented management of spatial development of united territorial communities (UTC) under the conditions of decentralization under the influence of economic consequences of the Covid-19 pandemic. The article aims to justify the problem-oriented approach in the management of UTC based on the development of a cognitive map of the problems of their development and modelling the problem-oriented management of community resources on the example of human resources. The problem-oriented approach to resource management focuses on solving a problem as a specific theoretical or practical problem, which in turn adaptability, flexibility, the ability to make timely management decisions using available resources. The cognitive map of the four groups of problems of UTC development was developed: problems of the spatial development of UTC and administrative-territorial structure; problems of socio-economic development based on self-sufficiency; problems of local self-government system; problems of rural territories development. The example of human resources scenarios of problem-oriented management of community resources at the macro-, meso-; micro-levels were offered. The hypothesis that the effect of measures “from below” will spread more rapidly than “from above” has been proved.